At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To complete the point-slope equation of the line passing through the points [tex]\((-9, 6)\)[/tex] and [tex]\((-7, -8)\)[/tex], we need to find the slope of the line and then use the point-slope form of a linear equation.
1. Find the slope: The slope [tex]\( m \)[/tex] of a line passing through two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is given by the formula:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Plugging in the given points [tex]\((-9, 6)\)[/tex] and [tex]\((-7, -8)\)[/tex]:
[tex]\[ m = \frac{-8 - 6}{-7 + 9} = \frac{-14}{2} = -7 \][/tex]
2. Use the point-slope form: The point-slope form of a linear equation is:
[tex]\[ y - y_1 = m (x - x_1) \][/tex]
Here, [tex]\( m = -7 \)[/tex] and the point [tex]\( (x_1, y_1) = (-9, 6) \)[/tex].
Substituting these values into the form:
[tex]\[ y - 6 = -7 (x + 9) \][/tex]
Thus, the completed point-slope equation of the line through [tex]\((-9, 6)\)[/tex] and [tex]\((-7, -8)\)[/tex] is:
[tex]\[ y - 6 = -7 (x + 9) \][/tex]
1. Find the slope: The slope [tex]\( m \)[/tex] of a line passing through two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is given by the formula:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Plugging in the given points [tex]\((-9, 6)\)[/tex] and [tex]\((-7, -8)\)[/tex]:
[tex]\[ m = \frac{-8 - 6}{-7 + 9} = \frac{-14}{2} = -7 \][/tex]
2. Use the point-slope form: The point-slope form of a linear equation is:
[tex]\[ y - y_1 = m (x - x_1) \][/tex]
Here, [tex]\( m = -7 \)[/tex] and the point [tex]\( (x_1, y_1) = (-9, 6) \)[/tex].
Substituting these values into the form:
[tex]\[ y - 6 = -7 (x + 9) \][/tex]
Thus, the completed point-slope equation of the line through [tex]\((-9, 6)\)[/tex] and [tex]\((-7, -8)\)[/tex] is:
[tex]\[ y - 6 = -7 (x + 9) \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.